Attitudes and beliefs about mental illness among relatives of patients with schizophrenia - Ajak Manguak Agau; Anne Bodilsen (South Sudan Medical Journal, 2017)
Background: Schizophrenia is a mental disease with inability to differentiate real from unreal. In many African cultures a traditional view on mental disease results in stigma, negative attitudes, and ignorance of the patient and their symptoms.